The Relationship Between The Level of Knowledge and Self-Care In Diabetes Mellitus Patients at The Tamamaung Public Health Center, Makassar City - Nur Wahyuni Munir (Sorume Health Sciences Journal, 2020)
Practice self-care in diabetic patients by eating a healthy diet, medication, blood glucose, and physical exercise for optimal health. This study aims to see the relationship between the level of knowledge and self-care in diabetes mellitus patients at the Puskesmas Tamamaung, Makassar City. This study used an analytic survey design with a cross sectional study approach. Determination of the sample using purposive sampling technique with a sample size of 41 respondents. The relationship test was performed using the Fisher Exact Test statistical test with a significance level of α 0.05. The results showed that patients with diabetes mellitus had 51.2% high knowledge, 36.6% moderate knowledge, and 12.2% low knowledge. In addition, patients with high self-care were 83% and low self-care was 17%. The conclusion of this study is that there is no relationship between knowledge and self-care in diabetes mellitus patients at the Puskesmas Tamamaung Makassar City (ρ = 0.347). Patient knowledge needs to be improved with regular health education, so that patients understand optimal diabetes mellitus self-care practices. Keywords:  Diabetes Mellitus, Level of Knowledge, Self Care